2014
DOI: 10.2495/978-1-78466-034-5/012
|View full text |Cite
|
Sign up to set email alerts
|

Liquefaction processes and characterization of liquefied products from waste woody materials in different acidic catalysts

Abstract: The liquefaction process is one of the promising techniques for effective utilization of woody biomass, for the lignocelluloses can be converted to liquid reactive material, as eco-polymeric materials. Japanese cedar (Cryptomeria Japonica), as an abundant waste softwood material, was selected and used in our wood liquefaction experiment. In order to investigate the basic characteristics and potentially harmful metal contents, the composition and metal elements of waste woody samples had been determined, and ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…To determine hollocellulose, all lignin should be removed, leaving the carbohydrates in place 29 . At 1.3 m trunk height, clone R1757 had the highest holocellulose content (Table 2).…”
Section: Chemical Propertiesmentioning
confidence: 99%
“…To determine hollocellulose, all lignin should be removed, leaving the carbohydrates in place 29 . At 1.3 m trunk height, clone R1757 had the highest holocellulose content (Table 2).…”
Section: Chemical Propertiesmentioning
confidence: 99%
“…It was clear that the liquefi ed products were composed of high molecular compounds, because the average molecular weights (polydispersity (Mw/Mn)) of the liquefi ed products were increased [27]. This indicated that the condensation reaction [28] might occur at the beginning of reaction due to the presence of the compounds.…”
Section: Molecular Weight Distribution Of Liquefi Ed Productmentioning
confidence: 92%
“…A conclusion could be inferred that the highest concentration of H + in the liquefaction system is sulfuric acid, followed by phosphoric acid, and oxalic acid is the lowest according to their dissociation constants [37]. Therefore, sulfuric acid has the best catalytic effect on the liquefaction of biomass materials, while oxalic acid has the worst [38]. Consequently, sulfuric acid was chosen as a catalyst to promote the liquefaction of cassava starch.…”
Section: Effect Of Liquefaction Parameters On Residue Ratementioning
confidence: 99%